Geochemical characteristics and reservoir continuity of Silurian Acacus in Ghadames Basin, Southern Tunisia. (November 2017) - Mahmoudi, S.; Mohamed, A. Belhaj; Saidi, M.; Rezgui, F.
Abstract: The present work is dealing with the study of lateral and vertical continuity of the multi-layers Acacus reservoir (Ghadames Basin-Southern Tunisia) using the distribution of hydrocarbon fraction. For this purpose, oil–oil and source rock–oil correlations as well as the composition of the light fractions and a number of saturate and aromatic biomarkers parameters, including C35/C34 hopanes and DBT/P, have been investigated. Based on the ratios of light fraction and their fingerprints, the Acacus reservoir from Well1 and Well2 have found to be laterally non-connected although the hydrocarbons they contain have the same source rock. Moreover, the two oil samples from two different Acacus reservoir layers crossed by Well3-A3 and A9, display a similar hydrocarbons distribution, suggesting vertical reservoir continuity. On the other hand, the biomarker distributions of the oils samples and source rocks assess a Silurian "Hot shale" that is the source rock feeding the Acacus reservoir. The biomarker distribution is characterized by high tricyclic terpanes contents compared to hopanes for the Silurian source rock and the two crude oils. This result is also confirmed by the dendrogram that precludes the Devonian source rocks as a source rock in the study area. Highlights: A study of maturity and depositional environment were performed with light fraction. Chromatographic data are used to study Acacus reservoir continuity. Oil-oil correlation based on GC data show the common origin of oils. Different biomarkers have been exploited in the correlation oil-source rock. The biomarker analysis shows that the oils are derived from Silurian hot shale.